Anti-Inflammatory Effects of Secondary Metabolites of Marine Pseudomonas sp. in Human Neutrophils Are through Inhibiting P38 MAPK, JNK, and Calcium Pathways - Yang, Shun-Chin (PLoS One, 2014)
Activated neutrophils play a significant role in the pathogenesis of many inflammatory diseases. The metabolites of marine microorganisms are increasingly employed as sources for developing new drugs; however, very few marine drugs have been studied in human neutrophils. Herein, we showed that secondary metabolites of marine Pseudomonas sp. (N11) significantly inhibited superoxide anion generation and elastase release in formyl-L-methionyl-L-leucyl-L-phenylalanine (FMLP)-activated human neutrophils, with IC(50) values of 0.67±0.38 µg/ml and 0.84±0.12 µg/ml, respectively. In cell-free systems, neither superoxide anion-scavenging effect nor inhibition of elastase activity was associated with the suppressive effects of N11. N11 inhibited the phosphorylation of p38 MAP kinase and JNK, but not Erk and Akt, in FMLP-induced human neutrophils. Also, N11 dose-dependently attenuated the transient elevation of intracellular calcium concentration in activated neutrophils. In contrast, N11 failed to alter phorbol myristate acetate-induced superoxide anion generation, and the inhibitory effects of N11 were not reversed by protein kinase A inhibitor. In conclusion, the anti-inflammatory effects of N11 on superoxide anion generation and elastase release in activated human neutrophils are through inhibiting p38 MAP kinase, JNK, and calcium pathways. Our results suggest that N11 has the potential to be developed to treat neutrophil-mediated inflammatory diseases.